2010
DOI: 10.1186/1939-4551-3-s2-s17
|View full text |Cite
|
Sign up to set email alerts
|

May We Strengthen the Human Natural Defenses with Bacterial Lysates?

Abstract: During the last twenty years bacterial lysates have gained a new interest and their use has obtained a progressively larger consensus in the medical practice. They are commonly used as immunomodulators, in order to up-regulate immune responses against infectious damages. As a matter of fact, the role of these lysate seems relevant in upper and lower respiratory tract infections prevention, frequently observed both in paediatric and elder ages, and which represent a relevant problem also in terms of socioeconom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The only differences observed were that the mechanical lysate induced higher levels of pro-inflammatory mediators in an alveolar cell line, and that the alkaline lysate required a further step of concentration during preparation to reach the same protein concentration than the mechanical. It has been suggested that PBLs prepared by mechanical disruption of the bacterial cell are more immunogenic than those prepared by chemical lysis of the cells ( 31 , 33 ). Still, here we showed that when both preparations have similar composition, they exerted similar biological effects.…”
Section: Discussionmentioning
confidence: 99%
“…The only differences observed were that the mechanical lysate induced higher levels of pro-inflammatory mediators in an alveolar cell line, and that the alkaline lysate required a further step of concentration during preparation to reach the same protein concentration than the mechanical. It has been suggested that PBLs prepared by mechanical disruption of the bacterial cell are more immunogenic than those prepared by chemical lysis of the cells ( 31 , 33 ). Still, here we showed that when both preparations have similar composition, they exerted similar biological effects.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial lysates or extracts (mostly polyvalent containing extracts of multiple species) are the products of bacterial and fungal cell lysis (cell disruption). Bacterial lysates in particular have been studied over several decades and are being used as potent immunostimulators/ immunomodulators for enhancing both innate and adaptive immunity [16][17][18][19][20][21][22]. Bacterial lysates are generally prepared by chemical (mainly alkaline cell lysis) or mechanical (lysis by high pressure shear or in bead mills) methods and they demonstrate therapeutic and prophylactic effects in the treatment of upper and lower respiratory tract infections (RTI) in both adults and paediatric patients [17][18][19][20].…”
Section: What Are Microbial Lysates and How Are They Related To The M...mentioning
confidence: 99%
“…Bacterial lysates are generally prepared by chemical (mainly alkaline cell lysis) or mechanical (lysis by high pressure shear or in bead mills) methods and they demonstrate therapeutic and prophylactic effects in the treatment of upper and lower respiratory tract infections (RTI) in both adults and paediatric patients [17][18][19][20]. In addition to their predominant use in the treatment of respiratory tract disorders like asthma, COPD and rhinitis, bacterial lysates have shown encouraging results in the treatment of various diseases like diverticulitis, rheumatoid arthritis, type 1 diabetes, inflammatory bowel disease, urinary tract infections, periodontitis, relapse of tuberculosis and food allergy [16][17][18][19][20][21][22]. Bacterial lysates are also effective against fungal and viral infections [23][24][25][26].…”
Section: What Are Microbial Lysates and How Are They Related To The M...mentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, mechanical cell disruption has proven to be an efficient method, achieving lysis of 80-100% of the bacteria (Cazzola et al, 2012a). As other authors have previously proposed, mechanical lysates contain particles that maintain several features of intact antigenic molecules, thus providing better interaction with Toll-like receptors which is one of the initial aims of these preparations (Villa et al, 2010;Cazzola et al, 2012a,b;Esposito et al, 2018;Triantafillou et al, 2019). However, the method has the limitation of heat generation which must be minimized to avoid protein denaturalization under the process and it is more expensive than alkaline lysis.…”
Section: Proteoglycans and Ribosomesmentioning
confidence: 99%